Connecting Unexplored Protein Crystal Structures to Enzymatic Function. Issue 1 (8th November 2012) - Steffen‐Munsberg, Fabian; Vickers, Clare; Thontowi, Ahmad; Schätzle, Sebastian; Tumlirsch, Tony; Svedendahl Humble, Maria; Land, Henrik; Berglund, Per; Bornscheuer, Uwe T.; Höhne, Matthias
<x xml:space="preserve">Abstract</x> Digging in the database: Four synthetically useful transaminases for which no function was known were studied by evaluating a set of eight amino donors and seven acceptors (see figure). The four enzymes differ substantially in their catalytic properties and substrate preferences. We also used the enzymes in the asymmetric synthesis of a range of chiral amines and observed excellent enantioselectivities and conversions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>